Short-wave run-ups of the 1611 Keicho tsunami along the Sanriku Coast - Yusuke Yamanaka; Yuichiro Tanioka (Progress in Earth and Planetary Science, 2022)
Abstract A tsunami generated by an earthquake that occurred off the east coast of Japan in 1611 was predominantly concentrated along the Sanriku Coast. The 1611 event produced its greatest observed tsunami height at Koyadori, 28.8 m, higher than that produced by other representative tsunamis at the same location such as the 2011 Tohoku and 1896 Meiji Sanriku tsunamis. The characteristics of the source that resulted in the remarkable tsunami height at Koyadori have been widely debated. In this study, we simulated the local intensification mechanism of the 1611 tsunami and derived some key characteristics of the earthquake that produced the intensification at Koyadori based on these results. First, we investigated the topographical inundation characteristics in representative areas on the Sanriku Coast, including Koyadori, by numerical means. By comparing the numerical results with the observed heights for the 1611 tsunami, we found that a simulated tsunami that was dominated by short-wave components yielded a promising reproduction of the observed heights. The development of a local resonance seemed a more likely cause for the observed local intensification at Koyadori than a single-pulse wave. These results suggested that the 1611 earthquake produced a tsunami dominated by short-wave components. Furthermore, the source must have been located far off the Tohoku coast near the Japan Trench axis to have had substantial short-wave components along the Sanriku Coast. Based on these findings, we constructed a source scenario for local intensification by investigating the characteristics of Green’s functions from single-point sources. The scenario involves two separate earthquake sources in shallow crustal areas at the plate interface of the subduction zone, resulting in a moment magnitude of 8.5. The tsunami produced by this source model, which reflected the characteristics of a tsunami earthquake, effectively reproduced the local intensification observed on the Sanriku Coast.